Zróżnicowanie flory roślin naczyniowych w uroczysku Rzepiszew - Woziwoda, Beata (Biuletyn Szadkowski, 2011)
The old forest complex of Rzepiszew (76.81 ha of land) is located in the east part of Szadek commune. It is surrounded by arable fields and meadows. At present it is a timber forest, but forest management is based on ecological rules. 260 vascular plant species forming 55 families have been found in this area during field research which was carried out in years 2006−2010. The identified species represent different types of growth (= life forms in Raunkiaer’s terminology) Hemicryptophytes have been found to dominate. The flora contains plants from various ecological groups classed according to light conditions, moisture of soil, soil acidity and soil trophy. Most of them are stenotopic plants – they have a limited (narrow) ecological amplitude. The true forest species are the most valuable components of flora. Seven among them are protected by law.